2020
DOI: 10.3390/foods9091203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Coatings on Preservation and Shelf Life of Fresh Chicken Breast Fillets Under Cold Storage

Abstract: Fresh poultry products such as chicken breast are very convenient for consumption due to their availability and nutritional and sensory characteristics but they have a short shelf life (3–5 days) due to their high water activity and propensity to microbial contamination and spoilage. In this work, the characteristics of edible coatings (EC) prepared from various formulations of guar gum (GG) and isolated soy protein were evaluated. From this evaluation, and due to the guar gum EC being the most suitable, antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…To obtain satisfactory film-forming solutions for active packaging of meat products, the conditions of preparation techniques, as well as storage under controlled temperature, as reported previously, should be established. Likewise, Garavito et al [118] evaluated guar gum and isolated soya protein to prepare edible coatings, and the blended films were infused with oregano oil and nisin as antimicrobial agents to use for the preservation of chicken breast fillets. The authors used plasticizer sorbitol and glycerol, and they observed that 0.4% (w/v) of guar gum and 1% (w/v) of plasticizer resulted in glossy, transparent, bright films.…”
Section: Brief Overview On the Preparation Techniques Of Green Coating And Film Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain satisfactory film-forming solutions for active packaging of meat products, the conditions of preparation techniques, as well as storage under controlled temperature, as reported previously, should be established. Likewise, Garavito et al [118] evaluated guar gum and isolated soya protein to prepare edible coatings, and the blended films were infused with oregano oil and nisin as antimicrobial agents to use for the preservation of chicken breast fillets. The authors used plasticizer sorbitol and glycerol, and they observed that 0.4% (w/v) of guar gum and 1% (w/v) of plasticizer resulted in glossy, transparent, bright films.…”
Section: Brief Overview On the Preparation Techniques Of Green Coating And Film Polymersmentioning
confidence: 99%
“…Reports showed that nisin, when incorporated in soya protein isolate-guar gum-blended films, exhibited an excellent inhibition zone against the formation of Pseudomonas spp. spores in wrapped chicken fillets [118].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…However, refrigerated meat is still perishable due to metabolic changes occurring during storage and microbial spoilage that result in physiological ageing and deterioration in the colour, texture, and flavour. The propensity of fresh meat products to microbial contamination and spoilage is increased due to its high water content, leading to a short shelf life (3-5 days) [4]. Refrigerated chicken meats showed a higher risk (p < 0.05) of Salmonella contamination during storage compared with other stages from chicken processing to retail [5].…”
Section: Introductionmentioning
confidence: 99%
“…Raeisi et al [ 82 ] used a sensory panel that comprised ten experienced subjects to evaluate sensory attributes of deep-fried chicken nugget samples. In a study by Garavito et al [ 27 ], cooked chicken breast fillets were evaluated by eight semi-trained panelists.…”
Section: Methodsmentioning
confidence: 99%
“…One source of natural antioxidants is oregano ( Origanum vulgare ) frequently selected in the case of poultry not only for its well-established antioxidant activity, but also for its antimicrobial properties and its sensory affinity with chicken taste. In a study by Garavito et al [ 27 ], oregano oil was added to the formulation of antimicrobial coating applied to fresh chicken breast fillets, and it was found that a significant extension of their shelf life (nine days vs. six days for untreated samples) was obtained. Boskovic et al [ 28 ] studied the antioxidant stability of minced pork treated with thyme and oregano essential oils (EOs) and packaged under vacuum and modified atmosphere and observed reduced lipid oxidation after two weeks’ storage.…”
Section: Introductionmentioning
confidence: 99%